PENGARUH MODAL KERJA DAN PENJUALAN TERHADAP LABA BERSIH PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020 - Dewi Mufaridah Ayuningsih; Merlyana Dwinda Yanthi (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine and analyze the effect of working capital and sales on net income. The object of this study is a telecommunications company listed on the IDX in the 2015-2020. This research uses quantitative methods, data collection using documentation methods, and data analysis using multiple linear regression analysis methods using the SPSS 23 application. The results of this study show that partially and simultaneously working capital and sales had a significant effect on net income in telecommunications company listed in the IDX in the 2015-2020. The results are in line with the objectives and functions of working capital and sales. Working capital serves to finance the company's daily operational activities to generate profits, while sales are the company's activities in selling products with the aim of obtaining profits. So it can be concluded that the higher the working capital and sales, the higher the company's net profit.